A mise en scène e influência hopperiana no cinema - Beatriz Conceição Fraga França (2021)
Analyzing the life and work of the American painter Edward Hopper, this dissertation pursues to identify the echoes of Hopper's work in cinema through the analysis of the pictorial and its influences on the filmic space. The technical aspects, composition, language, and meaning present in Hopper's works are considered, emphasizing the melancholy and alienation present in his works and how these are reconfigured into the cinematographic representation. This work also discusses why Hopper’s ethereal and spectral elements and atmosphere influence cinema. The research object was based on some of Hopper's paintings that were repeatedly reproduced in cinematographic works, such as House by the Railroad (1925); Nighthawks (1942); Automat (1927); Gas (1940), and Night Windows (1928), as well as some of his cinematographic representations, such as Shirley: Visions of Reality (2014), directed by Gustav Deutsch; Psycho (1960) and Rear Window (1954), both directed by Alfred Hitchcock, and Profondo Rosso (1975), directed by Dario Argento, among other works. This work sets one’s sights on identifying the recurrent visual elements of Hopper's work in cinema; to list the characteristics similar to these works and identify the context in which the Hopperian works are cinematically represented.